Pain therapy in the pediatric population - Białowąs, Edyta; Mazurek, Magdalena; Aghadi, Artur; Cuber, Iwona; Dybała, Ewelina (Journal of Education, Health and Sport, 2023)
Introduction: The assessment and treatment of pain in the pediatric population is a huge challenge for doctors and medical staff dealing with this group of patients. It is also one of the most important elements of pediatric care practice. There are many factors that contribute to the difficulty of assessing and managing pain in children, but the most important seems to be the lack of unified standards of care. In pain therapy, both pharmacotherapy and behavioral methods and psychological care are used. Purpose of the work: The aim of this work is to systematize the current state of knowledge in the field of pain therapy in the pediatric population, focusing particular attention on pharmacotherapy Materials and Evidence: We reviewed the literature available in the PubMed database using the following keywords: pediatric; pain therapy; analgesia Summary: Pain therapy in the pediatric population, despite the fact that it is often underestimated and insufficiently managed, is crucial both in terms of avoiding health complications and in the overall therapeutic process. Despite the presence of many drugs for pain therapy on the market, many of them are not approved for use in this group of patients. Knowledge of their mechanisms of action and predicting the impact on metabolism in a pediatric patient compared to an adult is crucial for the management of both acute and chronic pain syndromes. Despite the current knowledge, there is still a need for broader research on the possibility of the drugs used, their impact on the therapy process and side effects in the youngest patients.